Remote capture : digitising documentary heritage in challenging locations - Butterworth, Jody; Pearson, Andrew (Andrew F.); Sutherland, Patrick; Farquhar, Adam (Open field guides series, 2018)
"This is a must-read how-to guide if you are planning to embark on a scholarly digitisation project. Tailored to the specifications of the British Library's EAP (Endangered Archives Programme) projects, it is full of sound, practical advice about planning and carrying out a successful digitisation project in potentially challenging conditions. From establishing the scope of the project, via practical considerations about equipment, work routines, staffing, and negotiating local politics, to backing up your data and successfully completing your work, Remote Capture walks you through every stage. Bursting with helpful hints, advice and experiences from people who have completed projects everywhere around the globe from Latin America to Africa to Asia, this book offers a taste of the challenges you might encounter and the best ways to find solutions. With a particular focus on the process of digitisation, whether using a camera or a scanner, Remote Capture is invaluable reading for anybody considering such a project. It will be particularly useful to those who apply for an EAP grant, but the advice in these pages is necessary for anyone wondering how to go about digitising an archive."--Publisher's website